The awareness of safety management implementation with respect to industrialised building system (IBS)/ Aelyna Mohd Nasir. - Mohd Nasir, Aelyna (2006)
Safety management is an essential factor in construction industry. It is important to have a proper system to manage Occupational Safety and Health (OSH) at the workplace. On a national perspective, the basis of Occupational Safety and Health system lies in legislative framework. Compared to other acts and regulations, the Occupational Safety and Health Act (OSHA) 1994 is a new legislation. The OSHA had made significant improvement in the quality of safety and health in workplaces in Malaysia. There has been a marked change in the safety and health of the workforce since the enactment of the OSHA. The total number of accidents at the workplace had dropped by 58.2 percent over the 11 years period from 1993 to 2004. Over the last four years there was a steady decline in the number of industrial accidents with around 10 accidents per 1,000 workers in 2000 compared to seven accidents per 1,000 workers in 2004 (Bernama, June 28, 2005). However this rate is far behind the satisfactory level. In fact, from 1997 to 2003 the rate had remained in plateau of between 9.5 and 10.5 accidents per 1,000 workers.